Pour une agora politique partagée autour de la méditerranée (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO : 1. Liminaire - 2. Les transformations du droit de liberté religieuse - 3. Transformations européennes, circulation de modelés et “universalisme modeste” - 4 Pour une “saine osmose” entre sphère séculière étatique et sphère religieuse.For a shared political agora around the MediterraneanABSTRACT: The right to religious freedom is in profound transformation on both sides of the Mediterranean. While the Muslim presence shows European difficulties in the treatment of the collective dimensions of this right, the southern shore is confronted with the demands connected to the individualization of beliefs. On both sides, the challenge of freedom of conscience and religion and of the construction of pluralist constitutional democracies proposes ancient questions in renewed terms, soliciting a new rediscovery of the answers given by the universalistic constitutionalism of the second post-war period.